The Emerging Role of Circular RNAs in Prostate Cancer: A Systematic Review - Chao, Fan; Wang, Shiyu; Zhang, Cong; Han, Dunsheng; Xu, Guoxiong; Chen, Gang (Frontiers in Cell and Developmental Biology, 2021)
Prostate cancer is one of the most common malignant tumors that threaten the health of men. It is urgent to explore new molecular targets and develop new drugs for the treatment of prostate cancer. Circular RNAs (circRNAs) are aberrantly expressed in various malignant tumors. The dysregulated circRNAs are involved in the metastasis, tumor growth, drug resistance, and immunosuppression of malignant tumors. The present review systematically summarized publications concerning the biological implications of circRNAs in prostate cancer. The PubMed and Web of Science databases were used to retrieve publications concerning circRNAs and prostate cancer until June 16, 2021. The following keywords were used in the literature search: (circRNA OR circular RNA) AND prostate cancer. 73 publications were enrolled in the present systematic review to summarize the role of circRNAs in prostate cancer. The dysregulated and functional circRNAs were involved in the cell cycle, proliferation, migration, invasion, metastasis, drug resistance and radiosensitivity of prostate cancer. In addition, circRNAs could function through EVs and serve as prognostic and diagnostic biomarkers. Certain circRNAs were correlated with clinicopathological features of prostate cancer. A comprehensive review of the molecular mechanism of the tumorigenesis and progression of prostate cancer may contribute to the development of new therapies of prostate cancer in the future.